Thematic Integration Impairments in Primary Progressive Aphasia: Evidence From Eye-Tracking - Walenski, Matthew; Mack, Jennifer E.; Mesulam, M. Marsel; Thompson, Cynthia K. (Frontiers in Human Neuroscience, 2021)
Primary progressive aphasia (PPA) is a degenerative disease affecting language while leaving other cognitive facilities relatively unscathed. The agrammatic subtype of PPA (PPA-G) is characterized by agrammatic language production with impaired comprehension of noncanonical filler-gap syntactic structures, such as object-relatives (e.g., The sandwich that the girl ate [gap] was tasty), in which the theme (the sandwich) is displaced from the object position within the relative clause to a position preceding both the verb and the agent (the girl) and is replaced by a gap, associated with the filler. One hypothesis suggests that the observed deficits of these structures reflect impaired thematic integration, including impaired prediction of the thematic role of the filler and impaired thematic integration at the gap, but spared structure building (i.e., creation of the gap). In the current study we examined the on-line comprehension of object-relative and subject-relative clauses in healthy controls and individuals with agrammatic and logopenic PPA using eye-tracking. Eye-movement patterns in canonical subject-relative clause structures were essentially spared in both PPA groups. In contrast, eye-movement patterns in noncanonical object-relative clauses revealed delayed thematic prediction in both agrammatic and logopenic PPA, on-time structure building (i.e., gap-filling) in both groups, and abnormal thematic integration in agrammatic, but not logopenic, PPA. We argue that these results are consistent with the hypothesis that agrammatic comprehension deficits reflect impaired thematic integration.